Unusual prophages in Mycobacterium abscessus genomes and strain variations in phage susceptibilities. - Elizabeth D Amarh; Rebekah M Dedrick; Rebecca A Garlena; Daniel A Russell; Christian H Gauthier; Haley G Aull; Lawrence Abad; Deborah Jacobs-Sera; Chidiebere Akusobi; Eric J Rubin; Graham F Hatfull (PLoS ONE)
Mycobacterium abscessus infections are relatively common in patients with cystic fibrosis and are clinically challenging, with frequent intrinsic resistance to antibiotics. Therapeutic treatment with bacteriophages offers some promise but faces many challenges including substantial variation in phage susceptibilities among clinical isolates, and the need to personalize therapies for individual patients. Many strains are not susceptible to any phages or are not efficiently killed by lytic phages, including all smooth colony morphotype strains tested to-date. Here, we analyze a set of new M. abscessus isolates for the genomic relationships, prophage content, spontaneous phage release, and phage susceptibilities. We find that prophages are common in these M. abscessus genomes, but some have unusual arrangements, including tandemly integrated prophages, internal duplications, and they participate in active exchange of polymorphic toxin-immunity cassettes secreted by ESX systems. Relatively few strains are efficiently infected by any mycobacteriophages, and the infection patterns do not reflect the overall phylogenetic relationships of the strains. Characterization of these strains and their phage susceptibility profiles will help to advance the broader application of phage therapies for NTM infections.